Pengaruh PAD, Dana Perimbangan, Indeks Pembangunan Manusia, Jumlah Penduduk, dan PDRB terhadap Belanja Daerah Provinsi Jambi - Yois Nelsari Malau; Adelia Br Ginting; Alviona Paskah Riani Br Sitepu; Bernike Etimanta Br Munthe; Niarita Bukit (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this research was conducted to find out the impact of PAD, DP, IPM, JP, and GRDP on Regional Expenditure in Jambi Province 2017-2021. The population and sample totaled 55 observational data from 11 districts/cities with 5 years of observation as a sample, saturated sampling technique is the technique used in this study. As well as the data contained in this study using secondary data obtained from the Central Bureau of Statistics for Jambi Province 2017-2021. Tests on the research hypothesis were applied to the F test and T test. The results show that PAD and DP partially have an influence on regional spending, as well as HDI and GRDP as a whole does not affect the size of JP but is not significant. Meanwhile, simultaneously PAD, DP, HDI, JP and GRDP have an effect on regional spending.